TikTok as a Driver of Digital Marketing Performance: Examining the Role of Content and Viral Marketing in Shaping Purchase Intention - Hilda Elsera Br Sembiring; Rofiqoh Dewi; Dahri Yani Hakim Tanjung (International Enterprise Integration Association, 2026)
The rapid growth of social media platforms, particularly TikTok, has significantly transformed contemporary digital marketing practices. Nevertheless, the effectiveness of content marketing and viral marketing in influencing consumers’ purchase intention remains an important issue for further investigation. This study aims to analyze the influence of content marketing and viral marketing on purchase intention among TikTok users. A quantitative research approach was employed using a survey method involving 150 respondents in Medan Tuntungan selected through purposive sampling. The collected data were analyzed using multiple linear regression, supported by validity, reliability, and classical assumption tests to ensure data quality and model accuracy. The findings reveal that content marketing and viral marketing have a positive and significant effect on purchase intention, both partially and simultaneously. Among the two variables, content marketing demonstrates a stronger influence, indicating that informative, creative, and engaging content plays a crucial role in attracting consumer interest. Meanwhile, viral marketing contributes to increasing product exposure, consumer trust, and information dissemination efficiency. Furthermore, the coefficient of determination indicates that both variables explain a substantial proportion of the variance in purchase intention, although other external factors may also contribute. These findings provide practical implications for businesses, especially small and medium enterprises (SMEs), in developing effective TikTok-based digital marketing strategies through the integration of high-quality content and viral promotional approaches to enhance consumer purchase intention.